THE USE OF NUMBERED HEADS TOGETHER (NHT) LEARNING MODEL WITH SCIENCE, ENVIRONMENT, TECHNOLOGY, SOCIETY (SETS) APPROACH TO IMPROVE STUDENT LEARNING MOTIVATION OF SENIOR HIGH SCHOOL - Sutipnyo, B.; Mosik, M. (Department of Physics, Faculty of Mathematics and Natural Sciences, 2018)
This research was aimed to determine the increasing of students' motivation that has been applied by Numbered Heads Together (NHT) learning model with Science, Environment, Technology, Society (SETS) approach. The design of this study was quasi experiment with One Group Pretest-Posttest Design. The data of students’ learning motivation obtained through questionnaire administered before and after NHT learning model with SETS approach. In this research, the indicators of learning-motivation were facing tasks diligently, showing interest in variety of problems, prefering to work independently, keeping students’ opinions, and feeling happy to find and solve problems. Increasing of the students’ learning motivation was analyzed by using a gain test. The results showed that applying NHT learning model with SETS approach could increase the students’ learning motivation in medium categories.